Characteristics of Stomata and Leaf Thickness in Several Liliales Plants - Hasan, Rusdi; Nurzaman, Mohamad; Setiawati, Tia; Mutaqin, Asep Zainal (Florea : Jurnal Biologi dan Pembelajarannya, 2024)
This study examines the stomatal characteristics and leaf thickness of six species within the Liliales: Gloriosa superba, Sansevieria trifasciata, Aloe vera, Cordyline terminalis, Pleomele angustifolia, and Allium fistulosum. Stomatal density, type, and distribution were measured to understand their relationship with leaf morphology. The results show that Gloriosa superba has a stomatal density of 148.72/mm² and an index of 0.295, with thin leaves. Sansevieria trifasciata, with its thick, fleshy leaves, has a lower stomatal density of 15.39/mm² and an index of 0.031. Aloe vera, another species with thick leaves, has a stomatal density of 38.47/mm² and an index of 0.067. In contrast, Cordyline terminalis and *Pleomele angustifolia, which have thin leaves, exhibit higher stomatal densities of 192.31/mm² and 128.21/mm², respectively. Their stomatal indices are 0.092 for Cordyline terminalis and 0.163 for Pleomele angustifolia. Allium fistulosum also has thin leaves, with a stomatal density of 100/mm² and a high stomatal index of 0.390. The study reveals that species with thicker leaves tend to have lower stomatal densities, a feature that helps reduce water loss in arid environments. These findings contribute to a deeper understanding of plant adaptation mechanisms and have implications for improving water-use efficiency in agriculture and conservation efforts.